DAMPAK MEKANISME KERJA DEWAN PENGAWAS SYARIAH TERHADAP PENYALURAN ZIS DI LAZISNU BOYOLALI DAN LAZISMU SOLO - Rahmah Fadilah; Devi Indriyani; Bekti Ayu Ariastuti (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
The study aims to determine the mechanism of work and reporting of the results of DPS supervision on LAZISNU Boyolali and LAZISMU Solo. This research uses descriptive qualitative method, with a field research approach. It was found out that the mechanism of DPS's work both at LAZISNU Boyolali and LAZISMU Solo was to supervise LAZIS operational activities so that they were compliant with sharia rules and principles. The difference lies in reporting the results of DPS supervision which LAZISNU Boyolali reports the results to the regional level DSN and then SN at the regional level submits it to the central level DSN. It is different with LAZISMU Solo who reports the results of its supervision to LAZISMU at the regional level during RAKERPIMDA then LAZISMU at the central level when RAKORNAS, and only then LAZISMU central submits it to DSN-MUI.Keywords: Sharia Supervisory Board; Mechanism; LAZIS; Reporting